Security challenges and election administration in Nigeria’s fourth republic - Oni, Ebenezer Oluwole; Faluyi, Olumuyiwa Temitope; Asumu, Leo Otimeyin; Olutola, Adewale A. (Frontiers in Political Science, 2025)
Achieving meaningful development and success in any government endeavour will remain elusive without a robust and well-planned security architecture. Conducting credible, free and fair elections, guaranteeing the protection of election management officials and election materials, creating an enabling atmosphere for the electorate to cast their votes and ensuring that their votes count, are all possible within the framework of a safe and secured electoral environment. Observations have shown that security challenges in contemporary Nigeria are taking their tolls on the electoral process thus causing systematic disenfranchisement of the electorate, voter apathy, election manipulation, assaulting of election observers and destruction of their monitoring gadgets as well as the outright burning down of electoral management offices across the nation. It is against the foregoing that this article examined the implication of security challenges on election administration in Nigeria’s Fourth Republic that commenced in 1999. The study utilized qualitative research method with data gathered from secondary sources including books, journal articles, official government and non-governmental organisations’ documents, newspapers and internet materials while data were analysed using content analysis. The paper was anchored on state fragility as its theoretical framework. From its findings, the study showed that the underperformance of the election management body in Nigeria is compounded by the challenges of insecurity facing the nation including kidnapping, banditry and terrorism and exacerbated by the ineffectiveness of security agencies and their officials in addressing election insecurity in the country. The article concluded that a security unit be established within Nigeria’s election management structure to allow for long-term inclusive security mapping and planning as each election cycle unfolds.